THE ROLE OF ISLAMIC EDUCATION MANAGEMENT IN IMPROVING STUDENT ATTENDANCE AT FATHUL ULUM JUNIOR HIGH SCHOOL - Agas Mujtahid; Windasari (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to determine the role of Islamic Education Management in improving student attendance at SMP Fathul Ulum . Student attendance is an important element in the success of the learning process because good attendance will affect student understanding of the material , discipline , and learning achievement . Problems that often occur in educational institutions are still students who are late , absent without explanation , or lack motivation to learn . Therefore , good school management is needed through the application of Islamic education management functions . This study uses a descriptive qualitative method with data collection techniques through observation , interviews , and documentation . The results of the study indicate that the school applies management functions in the form of planning, organizing, implementing, and monitoring. Forms of activities carried out include creating regulations, daily attendance, cooperation with parents, character building, providing motivation, and routine evaluation of student attendance. With the application of Islamic education management, the school implements management functions in the form of planning , organizing , implementing , and monitoring . The forms of activities carried out include creating regulations , daily attendance , collaboration with parents , character building , providing motivation , and routine evaluation of student attendance . With the application of Islamic education management , the school implements management functions in the form of planning , organizing, implementing, and monitoring. which is good and based on Islamic values , the level of student attendance has increased gradually .